2011
DOI: 10.1093/nar/gkq1302
|View full text |Cite
|
Sign up to set email alerts
|

RhoA activation participates in rearrangement of processing bodies and release of nucleated AU-rich mRNAs

Abstract: Cytoplasmic ribonucleoprotein granules, known as processing bodies (P-bodies), contain a common set of conserved RNA-processing enzymes, and mRNAs with AU-rich elements (AREs) are delivered to P-bodies for translational silencing. Although the dynamics of P-bodies is physically linked to cytoskeletal network, it is unclear how small GTPases are involved in the P-body regulation and the ARE-mRNA metabolism. We found here that glucose depletion activates RhoA GTPase and alters the P-body dynamics in HeLa cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 53 publications
5
21
0
Order By: Relevance
“…In yeast, it has been demonstrated that various nutritional stresses lead to mRNA targeting to P-bodies, such as glucose depletion Takahashi et al, 2011), osmotic stress, UV light and acidic stress (Iwaki and Izawa, 2012). mRNA has been shown to enter Pbodies during translational shutoff, for either decay or for storage (Sheth and Parker, 2003;Brengues et al, 2005).…”
Section: Amino Acid Starvation Leads To Mrna-dependent P-body Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast, it has been demonstrated that various nutritional stresses lead to mRNA targeting to P-bodies, such as glucose depletion Takahashi et al, 2011), osmotic stress, UV light and acidic stress (Iwaki and Izawa, 2012). mRNA has been shown to enter Pbodies during translational shutoff, for either decay or for storage (Sheth and Parker, 2003;Brengues et al, 2005).…”
Section: Amino Acid Starvation Leads To Mrna-dependent P-body Assemblymentioning
confidence: 99%
“…P-bodies have been identified in lower and higher eukaryotes (Ingelfinger et al, 2002;van Dijk et al, 2002;Sheth and Parker, 2003;Cougot et al, 2004) and observations in yeast and mammalian cells have shown that P-body numbers depend on cellular conditions, such as osmotic stress, UV light or glucose deprivation. For instance, in the latter case, both yeast and mammalian P-bodies increase in size and number Takahashi et al, 2011;Iwaki and Izawa, 2012). P-body numbers and size also change as a result of the levels of free cytoplasmic mRNA .…”
Section: Introductionmentioning
confidence: 99%
“…20,25 PBs are a major site of ARE-mRNA decay; 26 our work shows that KapB mediates PB dispersion in a RhoA-dependent manner that correlates with the increased stability of AREmRNAs. 22,27,28 Notably, KapB is not alone in activating MK2 and RhoA; we and others have shown that the lytic gene product vGPCR, a constitutively active homolog of the human CXCR2 chemokine receptor, activates MK2 via Rac1-dependent MAPK activation, and independently activates RhoA by assembly of canonical cell surface G-protein-containing signaling complexes. 28 Thus, vGPCR also affects PB dynamics, ARE-mRNA stability and actin polymerization, but by distinct means.…”
Section: Kaposin B Activates the Stressresponsive Mk2-rhoa Signaling mentioning
confidence: 89%
“…29,30,[32][33][34][35] PBs are extremely dynamic, changing in size and number in response to cell cycle stage, nutrient availability, and stresses such as ultraviolet light (UV), osmotic shock and other inhibitors of global translation. 27,33,35,36 PBs can also transiently associate and exchange cargo with stress granules (SGs), cytoplasmic foci that triage stalled translationally-competent mRNPs. 34 PB assembly and disassembly is influenced by changes in the degradative capacity of the cell; for example, when 5 0 -3 0 exonucleolytic decay is prevented, the resulting accumulation of cytoplasmic mRNA awaiting destruction causes PB size and number to increase, whereas inhibiting de novo transcription or halting translation by trapping mRNA in polysomes has the opposite effect.…”
Section: Processing Bodies Control Inflammatory Mediator Release By Ecsmentioning
confidence: 99%
See 1 more Smart Citation